THE EFFECT OF RIFT SHOULDER EROSION ON STRATAL PATTERNS OF PASSIVE MARGINS: IMPLICATIONS FOR SEQUENCE STRATIGRAPHY - van Balen R.T.; van der Beek P.A.; Cloetingh S.A.P.L. (My University, 1995)
Numerical modelling indicates that the erosion of uplifted rift flanks at passive margins has a profound effect on offshore stratigraphic patterns. Flexural uplift, due to isostatic rebound in response to erosion, extends far into the basin and causes uplift of the shelf. As a result, the contemporaneously deposited sedimentary wedge displays a characteristic offlap pattern. When the rift shoulder is largely eroded, onlap-promoting mechanisms related to cooling of the lithosphere enable sediments to onlap onto the basin margin. The initial offlapping and subsequent onlapping strata form one complete second-order depositional sequence comprising a shelf-margin-, transgressive-and highstand-systems tract. The modelling inferences are in broad agreement with stratal patterns and basin geometries observed on the U.S. east coast, the southeastern Brazilian and southeastern Australian passive margins and the Transantarctic Mountains-Ross Sea Shelf system. The initial offlaps caused by erosion of rift shoulders have important implications for the deriviation of eustatic signals from coastal onlap patterns.